Anti-Candidal Marine Natural Products: A Review - Ganeshkumar, Arumugam [UNESP]; Gonçale, Juliana Caparroz [UNESP]; Rajaram, Rajendran; Junqueira, Juliana Campos [UNESP] (MDPI, 2023)
Candida spp. are common opportunistic microorganisms in the human body and can cause mucosal, cutaneous, and systemic infections, mainly in individuals with weakened immune systems. Candida albicans is the most isolated and pathogenic species; however, multi-drug-resistant yeasts like Candida auris have recently been found in many different regions of the world. The increasing development of resistance to common antifungals by Candida species limits the therapeutic options. In light of this, the present review attempts to discuss the significance of marine natural products in controlling the proliferation and metabolism of C. albicans and non-albicans species. Natural compounds produced by sponges, algae, sea cucumber, bacteria, fungi, and other marine organisms have been the subject of numerous studies since the 1980s, with the discovery of several products with different chemical frameworks that can inhibit Candida spp., including antifungal drug-resistant strains. Sponges fall under the topmost category when compared to all other organisms investigated. Terpenoids, sterols, and alkaloids from this group exhibit a wide array of inhibitory activity against different Candida species. Especially, hippolide J, a pair of enantiomeric sesterterpenoids isolated from the marine sponge Hippospongia lachne, exhibited strong activity against Candida albicans, Candida parapsilosis, and Candida glabrata. In addition, a comprehensive analysis was performed to unveil the mechanisms of action and synergistic activity of marine products with conventional antifungals. In general, the results of this review show that the majority of chemicals derived from the marine environment are able to control particular functions of microorganisms belonging to the Candida genus, which can provide insights into designing new anti-candidal therapies.
Keywords: antifungal properties; marine natural products; structural elucidation